Governing the firm in the social interest corporate governance reimagined - Casey, Catherine, 1958- (Routledge studies in corporate governance, 2024)
The corporate business enterprise is a core institution of capitalism. It holds immense political, economic, and cultural power in society. It mobilizes social and planetary resources to its utility in pursuit of private profit maximization and with little regard for social concerns. Its influence over so much of societal life and effects on the natural environment raise critical questions about the firm and its governance in democratic society. Various voices seek reforms of regulation and corporate governance practices to those shaped by the neoliberal policies persisting in the current decades. But prospects for amelioration within our current horizons of thinking appear elusive. This book contributes a distinctly social theoretical approach to the social problem of governing the firm. Its discussions complement debates in economics, politics, and law. Its critical social theorizations challenge conventional understandings of the firm and neoliberal legitimacies of its governance and posit alternatives. The book explores the social relations and moral fabric of the firm and the creativity of human action at work. It proposes a reimagined corporate governance premised on just recognition of that social vitality. It invites unprecedented collaboration for a robust participatory democracy for governing the firm and market action oriented to ecological and social sustainability.